2008
DOI: 10.1177/112067210801800427
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Anatomic Effect of Ranibizumab for Polypoidal Choroidal Vasculopathy

Abstract: Monthly intravitreal injection of ranibizumab for 3 months has a short-term beneficial anatomic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 6 publications
1
29
0
Order By: Relevance
“…In other reports related to intravitreal ranibizumab monotherapy for the treatment of PCV, 0–33% of polypoidal lesions showed regression [23,24,28]. Considering these reports and our study, we have come to the conclusion that combined treatment would be better than ranibizumab monotherapy for the regression of polyps, although some reported that 70% of polyps regressed on ICGA after intravitreal ranibizumab monotherapy [22]. …”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…In other reports related to intravitreal ranibizumab monotherapy for the treatment of PCV, 0–33% of polypoidal lesions showed regression [23,24,28]. Considering these reports and our study, we have come to the conclusion that combined treatment would be better than ranibizumab monotherapy for the regression of polyps, although some reported that 70% of polyps regressed on ICGA after intravitreal ranibizumab monotherapy [22]. …”
Section: Discussionmentioning
confidence: 57%
“…The reports of greater expression of VEGF in histopathology and increased VEGF in the aqueous humor have suggested the association of PCV and VEGF [16,17]. Some of the reports present that the anti-VEGF treatment might be a potential treatment to improve PCV [19,20,21,22,23,24,27]. Conversely, in terms of the polyp regression rate, anti-VEGF monotherapy could be inferior to PDT monotherapy or intravitreal anti-VEGF treatment combined with PDT [19,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, Terasaki et al 19 and Matsuoko et al 20 reported increased VEGF staining and expression on the vascular endothelium of PCV specimens. Initial clinical experience suggests that PCV respond well to anti-VEGF therapy, with rapid resolution of retinal thickening and exudate accumulation, 42,43 and increase in vision. 44 However, both Gomi et al 45 and Lai et al 46 reported that although anti-VEGF monotherapy reduces macular thickness and improved vision in patients with PCV, the majority of the polyps remained.…”
Section: Anti-vascular Endothelial Growth Factor Therapy For Pcvmentioning
confidence: 99%
“…Results with this smaller molecular weight compound are promising, showing regression of polypoidal changes (16,17) . A combination of PDT therapy and ranibizumab could provide a good alternative, by reducing the number of injections needed relative to that used in other anti-VEGF monotherapy.There are also reports of phototrombosis of neovessels, mediated by indocyanine green (18) .…”
Section: Introductionmentioning
confidence: 98%